PERFORMANCE AND ATTITUDE TOWARDS PHYSICAL ACTIVITY AMONG VIRTUAL WALKATHON PARTICIPANTS IN THE POST-PANDEMIC PERIOD - ALEJANDRIA, Warlen Ruzgal (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: The “new normal” has defined societal functioning in recent years and remains a crucial consideration as communities continue their path toward recovery and adaptation. Strategic disruption-proof wellness initiatives were explored to strengthen readiness of institutions. Objective: This study was conducted to find out the actual performance and attitude towards physical activity among the participants of a virtual walkathon in the post-pandemic period. Material and Methods: This one-group pretest–posttest quasi-experimental study involved 211 college students who had completed the requirements for inclusion. The participants had to have an internet connection and a pedometer app installed on their phones and were required to complete the Attitude Towards Physical Activity questionnaire before and after the activity. Frequency, percentage, mean, and standard deviation were used in analyzing the data. Tests such as the Wilcoxon Signed Ranks, Kruskal-Wallis, Mann-Whitney and the Spearman's Rho were utilized in comparing and finding the difference and relationships in the variables. Discussion: Results revealed a significant difference in all the sub-domains of the attitude towards physical activity among the participants when responses were compared before and after the intervention. Likewise, it shows that age have significantly affected the actual performance of the participants. There is an inverse relationship between the actual performance and the attitude towards physical activity particularly in the physical activity as a social experience. Conclusions: The findings revealed that active participation in innovative activities can foster desirable attitudes toward physical activity, thereby promoting desirable health practices and supporting the institutionalization of wellness programs.